Respuesta :
[tex]\bf tan\left[ 2cos^{-1}(x) \right]\implies tan\left[ 2cos^{-1}\left( \frac{x}{1} \right) \right]
\\\\\\
\textit{if we say }cos^{-1}\left( \frac{x}{1} \right)=\theta\textit{ that means }tan\left[ 2cos^{-1}\left( \frac{x}{1} \right) \right]\iff tan(2\theta)\\\\
-----------------------------\\\\
cos^{-1}\left( \frac{x}{1} \right)=\theta\implies cos(\theta)=\cfrac{x}{1}\cfrac{\leftarrow adjacent=a}{\leftarrow hypotenuse=c}\\\\
-----------------------------\\\\
[/tex]
[tex]\bf \textit{again, using the pythagorean theorem to get the opposite side} \\\\\\ c^2=a^2+b^2\implies \pm\sqrt{c^2-a^2}=b\implies \pm\sqrt{1^2-x^2}=b \\\\\\ \pm\sqrt{1-x^2}=b\\\\ -----------------------------\\\\ tan(2\theta)=\cfrac{2tan(\theta)}{1-tan^2(\theta)}\implies tan(2\theta)=\cfrac{2\cdot \frac{\pm\sqrt{1-x^2}}{x}}{1-\left( \frac{\pm\sqrt{1-x^2}}{x} \right)^2} \\\\\\[/tex]
[tex]\bf tan(2\theta)=\cfrac{\frac{\pm2\sqrt{1-x^2}}{x}}{1-\frac{1-x}{x}}\implies tan(2\theta)=\cfrac{\frac{\pm2\sqrt{1-x^2}}{x}}{\frac{x-1+x}{x}} \\\\\\ tan(2\theta)=\cfrac{\pm2\sqrt{1-x^2}}{x}\cdot \cfrac{x}{2x-1} \implies tan(2\theta)=\cfrac{\pm 2\sqrt{1-x^2}}{2x-1}[/tex]
[tex]\bf \textit{again, using the pythagorean theorem to get the opposite side} \\\\\\ c^2=a^2+b^2\implies \pm\sqrt{c^2-a^2}=b\implies \pm\sqrt{1^2-x^2}=b \\\\\\ \pm\sqrt{1-x^2}=b\\\\ -----------------------------\\\\ tan(2\theta)=\cfrac{2tan(\theta)}{1-tan^2(\theta)}\implies tan(2\theta)=\cfrac{2\cdot \frac{\pm\sqrt{1-x^2}}{x}}{1-\left( \frac{\pm\sqrt{1-x^2}}{x} \right)^2} \\\\\\[/tex]
[tex]\bf tan(2\theta)=\cfrac{\frac{\pm2\sqrt{1-x^2}}{x}}{1-\frac{1-x}{x}}\implies tan(2\theta)=\cfrac{\frac{\pm2\sqrt{1-x^2}}{x}}{\frac{x-1+x}{x}} \\\\\\ tan(2\theta)=\cfrac{\pm2\sqrt{1-x^2}}{x}\cdot \cfrac{x}{2x-1} \implies tan(2\theta)=\cfrac{\pm 2\sqrt{1-x^2}}{2x-1}[/tex]
Answer: The algebraic expression for the given expression is [tex]\frac{\pm 2x^{2}\sqrt{1-x^2} }{2x^{2}-1}[/tex].
Step-by-step explanation:
Let us assume [tex]cos^{-1} x= y\\[/tex] ⇒ [tex]cosy=x=\frac{x}{1}[/tex]
⇒[tex]tany=\pm \frac{\sqrt{1-{x^{2}}} }{x}[/tex]
[tex][cosy=\frac{x}{1} =\frac{base}{hypotenuse} ,which\: means, tany = \frac{perpendicular}{base} =\frac{hypotenuse^2-base^2}{base} ][/tex]
Now,
[tex]x.tan(2cos^{-1}x)= x.tan(2y)[/tex]
[tex]=x.\frac{2tany}{1-tan^{2}y}[/tex]
[tex]=x.\frac{\pm 2\sqrt{1-x^{2}}/x }{1-\frac{1-x^{2}}{x^2} }[/tex]
[tex]=\frac{\pm 2 x^{2}\sqrt{1-x^2} }{2x^{2}-1}[/tex]
Thus, [tex]x.tan(2cos^{-1}x)=[/tex][tex]\frac{\pm 2 x^{2}\sqrt{1-x^2} }{2x^{2}-1}[/tex]
Learn more about Trigonometry:
https://brainly.com/question/13729598